2014
DOI: 10.1890/es14-00058.1
|View full text |Cite
|
Sign up to set email alerts
|

Belowground bud banks of tallgrass prairie are insensitive to multi‐year, growing‐season drought

Abstract: Abstract. In tallgrass prairie plant communities, new shoots are recruited from belowground bud banks, often in response to disturbance. We explored the contribution of belowground bud banks to grassland stability when perturbed by severe drought. We sought to quantify changes in bud bank density and demography, assess the contribution of the bud bank to aboveground net primary productivity, and compare shifts in above-and belowground plant community structure in response to drought. We experimentally reduced … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
27
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(30 citation statements)
references
References 49 publications
1
27
2
Order By: Relevance
“…The ratio of buds per shoot we observed in response to drought and grazing treatments agreed with previous reports. In previous work, we found that the number of buds per shoot did not change with drought or irrigation relative to ambient conditions (VanderWeide et al 2014). In a separate study, we found that grazing reduced the number of buds per shoot for grasses by 15-25 % in 3 of the 4 years observed (VanderWeide 2013).…”
Section: Mechanism Of Changes In Bud Densitymentioning
confidence: 72%
“…The ratio of buds per shoot we observed in response to drought and grazing treatments agreed with previous reports. In previous work, we found that the number of buds per shoot did not change with drought or irrigation relative to ambient conditions (VanderWeide et al 2014). In a separate study, we found that grazing reduced the number of buds per shoot for grasses by 15-25 % in 3 of the 4 years observed (VanderWeide 2013).…”
Section: Mechanism Of Changes In Bud Densitymentioning
confidence: 72%
“…The strong drought responses observed here in the year of drought agree with the range of biomass responses reported in other grassland drought studies (Bloor & Bardgett, ; Frank et al., ), and may reflect the inability of buffering mechanisms to operate under the intense water stress associated with strong pulse drought events (De Boeck et al., ). Previous grassland studies have also reported fast biomass recovery after severe, one‐time drought events in humid and arid climates (Hoover et al., ; Mariotte et al., ; Yang et al., ); fast recovery is possible when soil moisture has been recharged after drought, as belowground plant meristems are highly resistant to drought (VanderWeide, Hartnett, & Carter, ; Volaire, Barkaoui, & Norton, ). In our study, fast recovery may have been enhanced by high carbohydrate reserves (Volaire et al., ) and relatively low plant mortality during drought.…”
Section: Discussionmentioning
confidence: 95%
“…For example, high drought resistance and phenotypic plasticity (Petru et al, ) may enable reproduction even under limited precipitation. Additional mechanisms, such as seed banks (Vanderweide, Hartnett, & Carter, ) and large seed size (Metz & Tielbörger, ), buffer catastrophic years and detrimental effects of environmental variation on population growth. Recently, a novel evidence indicated that in these ecosystems along the duration gradient, an increase in community nutrient, primarily driven by species turnover, has been shown to enhance their resistance to long‐term stress (Luo et al, ).…”
Section: Discussionmentioning
confidence: 99%